Intensive care unit burden is associated with increased mortality in critically ill COVID‐19 patients. Issue 3 (28th December 2022) - Didriksson, Ingrid; Leffler, Märta; Spångfors, Martin; Lindberg, Sarah; Reepalu, Anton; Nilsson, Anna; Cronqvist, Jonas; Andertun, Sara; Nelderup, Maria; Jungner, Mårten; Johnsson, Patrik; Lilja, Gisela; et al.
Abstract: Background: Traditional models to predict intensive care outcomes do not perform well in COVID‐19. We undertook a comprehensive study of factors affecting mortality and functional outcome after severe COVID‐19. Methods: In this prospective multicentre cohort study, we enrolled laboratory‐confirmed, critically ill COVID‐19 patients at six ICUs in the Skåne Region, Sweden, between May 11, 2020, and May 10, 2021. Demographics and clinical data were collected. ICU burden was defined as the total number of ICU‐treated COVID‐19 patients in the region on admission. Surviving patients had a follow‐up at 90 days for assessment of functional outcome using the Glasgow Outcome Scale‐Extended (GOSE), an ordinal scale (1–8) with GOSE ≥5 representing a favourable outcome. The primary outcome was 90‐day mortality; the secondary outcome was functional outcome at 90 days. Results: Among 498 included patients, 74% were male with a median age of 66 years and a median body mass index (BMI) of 30 kg/m 2 . Invasive mechanical ventilation was employed in 72%. Mortality in the ICU, in‐hospital and at 90 days was 30%, 38% and 39%, respectively. Mortality increased markedly at age 60 and older. Increasing ICU burden was independently associated with a two‐fold increase in mortality. Higher BMI was not associated with increased mortality. Besides age and ICU burden, smoking status, cortisone use, Pa CO2 >7 kPa, and inflammatory markers on admission were independent factors of 90‐day mortality. Lower GOSE at 90 days was associated with a longer stay in the ICU. Conclusion: In critically ill COVID‐19 patients, the 90‐day mortality was 39% and increased considerably at age 60 or older. The ICU burden was associated with mortality, whereas a high BMI was not. A longer stay in the ICU was associated with unfavourable functional outcomes at 90 days.